3/8(p-8)+1/2p=(p-6)

Simple and best practice solution for 3/8(p-8)+1/2p=(p-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/8(p-8)+1/2p=(p-6) equation:



3/8(p-8)+1/2p=(p-6)
We move all terms to the left:
3/8(p-8)+1/2p-((p-6))=0
Domain of the equation: 8(p-8)!=0
p∈R
Domain of the equation: 2p!=0
p!=0/2
p!=0
p∈R
We calculate fractions
-((p-6))+6p/(16p^2-128p)+(8pp/(16p^2-128p)=0
We calculate terms in parentheses: -((p-6)), so:
(p-6)
We get rid of parentheses
p-6
Back to the equation:
-(p-6)
We calculate terms in parentheses: +(8pp/(16p^2-128p), so:
8pp/(16p^2-128p
We multiply all the terms by the denominator
8pp
Back to the equation:
+(8pp)
We get rid of parentheses
-p+6p/(16p^2-128p)+8pp+6=0
We multiply all the terms by the denominator
-p*(16p^2-128p)+6p+8pp*(16p^2-128p)+6*(16p^2-128p)=0
We add all the numbers together, and all the variables
6p-p*(16p^2-128p)+8pp*(16p^2-128p)+6*(16p^2-128p)=0
We multiply parentheses
-16p^3+128p^2+128p^3-1024p^2+96p^2+6p-768p=0
We do not support eppression: p^3

See similar equations:

| -12n-19=49 | | 2/(x-1)+5=17/(x-1) | | (x-8)(X+4)=(x-4)(x-3) | | 2x(x+3)=32 | | 8(2x-6)=12 | | 4x^2+13x-4x^2=3 | | 4K=12+2z | | -x)+x=22+x | | 8x+2+5x^2=4 | | Y=27000x0.15^5 | | -2z=-68 | | -5x+3(5x-11)=57 | | 3|x|-66=0 | | 5(3m-(2)+4m= | | 2(t+1)=9 | | -1-1(1-7x)=5(2x+8) | | m+15=-18 | | -27=n-14 | | 3x-6=18+4 | | 77+x+26+x-3=180 | | x-(x-12)=58 | | -3(p-(4-2p))=1 | | 11n=22n | | x/20+2=7 | | 3/4x-5=1/2x+9 | | 3(2a+1)=11(a-2 | | -12+b=-10 | | 5+2n=-6+7n | | 6y+2=5y+7=13y-3 | | 0.09*(100-x)+0.4x=25 | | 12v+10v+14=80.v= | | -5y+21=76 |

Equations solver categories